Vitamin D deficiency may predict a poorer outcome of IgA nephropathy. Issue 1 (December 2016) - Li, Xiao-Hua; Huang, Xin-Ping; Pan, Ling; Wang, Cheng-Yu; Qin, Ju; Nong, Feng-Wei; Luo, Yu-Zhen; Wu, Yue; Huang, Yu-Ming; Peng, Xi; Yang, Zhen-Hua; Liao, Yun-Hua
Abstract Background Experimental studies showed that 25-hydroxy-vitamin D [25(OH)D] deficiency (defined as 25-hydroxy-vitamin D < 15 ng/ml) has been associated with CKD progression. Patients with IgA nephropathy have an exceptionally high rate of severe 25(OH)D deficiency; however, it is not known whether this deficiency is a risk factor for progression of IgA nephropathy. We conducted this study to investigate the relationship between the plasma level of 25(OH)D and certain clinical parameters and renal histologic lesions in the patients with IgA nephropathy, and to evaluate whether the 25(OH)D level could be a good prognostic marker for IgA nephropathy progression. Methods A total of 105 patients with biopsy-proven IgA nephropathy were enrolled between 2012 and 2015. The circulating concentration of 25(OH)D was determined using serum samples collected at the time of biopsy. The primary clinical endpoint was the decline of estimated glomerular filtration rate (eGFR; a 30 % or more decline compared to the baseline). Results Mean eGFR decreased and proteinuria worsened proportionally as circulating 25(OH)D decreased (P  < 0.05). The 25(OH)D deficiency was correlated with a higher tubulointerstitial score by the Oxford classification (P  = 0.008). The risk for reaching the primary endpoint was significantly higher in the patients with a 25(OH)D deficiency compared to those with a higher level of 25(OH)D (P  = 0.001). As evaluated using the Cox proportional hazards model, 25(OH)D deficiency was found to be an independent risk factor for renal progression [HR 5.99, 95 % confidence intervals (CIs) 1.59–22.54, P  = 0.008]. Conclusion A 25(OH)D deficiency at baseline is significantly correlated with poorer clinical outcomes and more sever renal pathological features, and low levels of 25(OH)D at baseline were strongly associated with increased risk of renal progression in IgAN.